1984
DOI: 10.1177/001440298405000602
|View full text |Cite
|
Sign up to set email alerts
|

The Readability of P.L. 94–142 Parent Materials: Are Parents Truly Informed?

Abstract: P.L. 94–142 requires that parents become involved in the educational decision-making of their handicapped child. For parents to become involved, they need to be familiar with the various complexities of the law so they can make informed decisions about their child's education. State and local education agencies inform parents primarily through printed materials. This study surveyed materials used by the 50 states and evaluated their comprehensibility. A computer program, using four common readability formulas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 10 publications
1
33
0
Order By: Relevance
“…Pruitt's analysis determined that the reading difficulty of the documents and forms averaged Grade 12, exceeding the reading grade level of the average parent in her sample (Grade 9) by three grade levels. Finally, Roit and Pfohl (1984) conducted a readability assessment of parental rights manuals used by 25 state educational agencies, using four different readability formulas: Flesch, Fog, Dale-Chall, and New Reading Ease. They concluded that parents needed at least a sixth grade education to be able to understand the manuals.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Pruitt's analysis determined that the reading difficulty of the documents and forms averaged Grade 12, exceeding the reading grade level of the average parent in her sample (Grade 9) by three grade levels. Finally, Roit and Pfohl (1984) conducted a readability assessment of parental rights manuals used by 25 state educational agencies, using four different readability formulas: Flesch, Fog, Dale-Chall, and New Reading Ease. They concluded that parents needed at least a sixth grade education to be able to understand the manuals.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Many documents evaluated within the body of research were publicly available such as parent brochures about attention deficit hyper activity disorder (ADHD; Singh, 1995) and electronically available Parents' Rights documents (Fitzgerald & Watkins, 2006). Prior to computer-based technologies, such as the Internet, authors requested state agencies (Roit & Pfohl, 1984) and schools (Mavrogenes, 1988a(Mavrogenes, , 1988b to mail hard copies of written communications for evaluation. In …”
Section: Identifying Readability Studies For Reviewmentioning
confidence: 99%
“…Roit and Pfohl (1984) conducted the first systematic analysis of the accessibility of informational parent documents to understand the appropriateness of such communication methods when considering parent education and literacy levels. The authors referenced the U.S. Bureau of Census and a nationwide survey from the U.S. Educational Testing Services (see Roit & Pfohl, 1984) to suggest anything written above ninth grade would be inappropriate for parents, especially given that grade level completion does not necessarily equate to reading grade level ability. Roit and Pfohl (1984) recognized the number of parents reading below ninth grade was unknown at the time of the study and theorized that school personnel make naïve or irresponsible assumptions about parents' ability to read and comprehend print materials each time they ask parents to give their informed consent.…”
Section: Appropriate Readability Levelsmentioning
confidence: 99%
“…Parents are expected to be actively involved in assessment, planning, and program evaluation (Gilliam & Coleman, 1981). Yet, in reality, parents have tended to play a passive role (Bell-Nathaniel, 1979;Lynch & Stein, 1982;Marion, 1980;Roit & Pfohl, 1984). In conferences, their role is reported to be mainly the giving and receiving of information (Lusthaus, Lusthaus, & Gibbs, 1981).…”
mentioning
confidence: 99%
“…In conferences, their role is reported to be mainly the giving and receiving of information (Lusthaus, Lusthaus, & Gibbs, 1981). Conjecture about the reasons for passive involvement of parents includes lack of parental knowledge (Goldstein, Strickland, Turnbull, & Curry, 1980), discomfort in school interactions (Dembinski & Mauser, 1977), confusion about the parental role (Hoff, Fenton, Yoshida, & Kaufman, 1978), high readability and comprehensibility levels of written communications to parents (Roit & Pfohl, 1984), uncertainty about how their child functions in the educational setting (Abramson, Willson, Yoshida, & Hagerty, 1983), and unfavorable attitudes toward parental participation by educational personnel (Yoshida, Fenton, Kaufman, & Maxwell, 1978).…”
mentioning
confidence: 99%